Strategi Guru Dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Akidah Akhlak MTSN 1 Katingan - Sartika, Yeni; M Ali Sibram Malisi; Muhammad Redha Anshari (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This study aims to analyze the strategies implemented by teachers at MTsN 1 Katingan to increase students' learning interest in the Akidah Akhlak subject. It also identifies the supporting and inhibiting factors in the implementation of these strategies. The research uses a qualitative descriptive method with data collected through observation, interviews, and documentation. The subjects include Akidah Akhlak teachers, the school principal, and Class VII A students. Data validation was conducted through source triangulation, while data analysis involved data collection, reduction, presentation, and conclusion. The results indicate that teachers employ various strategies to enhance learning interest, such as using creative and interactive methods, integrating relevant learning media, and utilizing school support through adequate facilities. Supporting factors include school policies, innovative teaching approaches, and parental involvement. Meanwhile, the obstacles found are the difficulty of understanding and applying the material, low student engagement, and limited learning facilities. These findings highlight the importance of a collaborative approach involving teachers, schools, and parents to foster students' interest in religious education.